Estructura de las asociaciones de las estrellas de mar (Asteroidea) en arrecifes rocosos del Golfo de California, México - Reyes Bonilla, Héctor; González Azcárraga, Adriana; Rojas Sierra, Aracely (Revista de Biología Tropical, 2005)
Sea Star (Asteroidea) assemblage structures on the rocky reefs of the Gulf of California, Mexico. Sea stars are invertebrates that play relevant roles in rocky and coral reefs: they occupy different levels in food webs and may act as top predators. There are numerous studies on taxonomy and biogeography of the class in the eastern tropical Pacific, but information about the attributes and composition of its assemblages is scant. The objectives of this study were the examination and comparison of asteroid community structure from four regions of the Gulf of California, México, characterized by the presence of rocky reefs, and the search for possible associations between pairs of species. In August 2004 we visited four locations in the western gulf: Bahía de Los Angeles (29º N), Santa Rosalía (27º N), Loreto (26º N) and La Paz (24º N), and censuses sea stars using 50 m2 belt transects (N=93). Abundance and species richness was estimated, as well as diversity (H’), evenness (J’) and taxonomic distinctness (Δ*); then, all variables were compared among regions with analysis of variance. In addition, an ordination analysis was run looking for groups of locations with similar faunistic composition. Our results showed that Loreto Bay had the highest richness and abundance of asteroids, probably because it presents a large number of habitats and multiple food sources; these conditions seem to favor the occurrence of rare species and of detritivores. However, there were no significant interregional differences among ecological indices, nor we detected groups of locations singled out because of its species composition. Thus, community structure of sea stars in rocky areas of the Gulf of California is quite homogeneous and do not change with latitude. This is a consequence of the fact that all regions under analysis had the species Phataria unifascialis and Pharia pyramidatus as dominant in number. There were significant positive associations between three pairs of species: apparently, competition is not particularly relevant to control sea star community structure in the gulf. Rev. Biol. Trop. 53(Suppl. 3): 233-244. Epub 2006 Jan 30.